2016
DOI: 10.1021/acs.iecr.6b00596
|View full text |Cite
|
Sign up to set email alerts
|

An Insight into the Temperature Field and Particle Flow Patterns in a Fluidized Bed Reactor for Nonpelletizing Polyethylene Process Using a 3D CFD-PBM Model

Abstract: This work aims at exploring the temperature and polyethylene (PE) particle flow patterns in a pilot-plant fluidized bed reactor via 3D CFD modeling approach. A Eulerian–Eulerian model involving ethylene polymerization kinetics is integrated with population balance model to investigate the issues for both traditional pelletizing PE process (TPPP) and nonpelletizing PE process (NPPP). The results show that the regions with large temperature gradients have been observed in top area. The revealed particle flow pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Results showed that particle growth due to polymerization has a remarkable influence on flow fields and solid distribution in the reactor; moreover, particle breakage led to a reduction of average particle size and to an increased axial expansion of the bed. The same research group [ 146 ] further improved the model by adopting a 3D schematization of the reactor; validation was carried out by comparing pressure drops and bed axial height.…”
Section: Macroscale Modeling With Computational Fluid Dynamicsmentioning
confidence: 99%
“…Results showed that particle growth due to polymerization has a remarkable influence on flow fields and solid distribution in the reactor; moreover, particle breakage led to a reduction of average particle size and to an increased axial expansion of the bed. The same research group [ 146 ] further improved the model by adopting a 3D schematization of the reactor; validation was carried out by comparing pressure drops and bed axial height.…”
Section: Macroscale Modeling With Computational Fluid Dynamicsmentioning
confidence: 99%
“…Although significant achievements have been made, the CFD–PBE simulation of stirred tank under various conditions using different crystallization technology still needs extensive research. Most of the articles applied the method of moments or its derivatives to solve the PBE; ,, though computationally efficient, the real particle size distribution could not be obtained. The PSD curve exhibits a double peak or shows a sharp change, resulting from the deconvolution algorithm.…”
Section: Introductionmentioning
confidence: 99%